The Relationship between Knowledge and Dietary Habit with Incidence Chronic Energy Deficiency in the Pregnant Women in the Working Area Talise City of Palu - Sri Ulfiani Maskur; Budiman Budiman; Ayu Lestari (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
One of the nutritional problems in pregnant women, namely chronic energy deficiency. The lack of regular energy is the condition of pregnant women who suffer from the lack of long-lasting food (chronic) with various health disorders. Pregnant women should be pregnant to fulfill nutritional intake not to occur chronic energy deficiency (this study's purpose is the relationship between knowledge and dietary habit with chronic energy deficiency incidence in pregnant women in the Talise Public Health Center. The type of analytical research surveys using a cross-sectional approach. This research has been implemented in the puuskesmas Talise city in Palu from June until Juli 2020. The results showed that of the two independent variables, they were not related to chronic energy deficiency. The results of statistical tests for knowledge P-value = 0.775, dietary pattern P-value = 0.463. In this study, conclusions are expected to provide healthcare workers with more attention to the healthy food consumption fan that healthy during pregnancy and conduct self-examination to prevent pregnant women at risk of a shortage of chronic energy deficiency. It is recommended that mothers keep looking for information about mothers' nutritional value during pregnancy and consume food and beverages that are of adequate nutritional needs during the inevitable hamilager of less chronic energy during pregnancy.